2009
DOI: 10.1093/hmg/ddp128
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mutations in the glycogen debranching enzyme found in glycogen storage disease type III lead to impairment in diverse cellular functions

Abstract: Glycogen storage disease type III (GSDIII) is a metabolic disorder characterized by a deficiency in the glycogen debranching enzyme, amylo-1,6-glucosidase,4-alpha-glucanotransferase (AGL). Patients with GSDIII commonly exhibit hypoglycemia, along with variable organ dysfunction of the liver, muscle or heart tissues. The AGL protein binds to glycogen through its C-terminal region, and possesses two separate domains for the transferase and glucosidase activities. Most causative mutations are nonsense, and how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…1). This makes a pathogenic effect of these mutations on GDE function very probable (Cheng et al 2009). As the c.3911delA, p.Asn1304fs causes a frameshift with the new reading frame ending in a stop codon at position 10, this is considered to be a pathogenic mutation as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). This makes a pathogenic effect of these mutations on GDE function very probable (Cheng et al 2009). As the c.3911delA, p.Asn1304fs causes a frameshift with the new reading frame ending in a stop codon at position 10, this is considered to be a pathogenic mutation as well.…”
Section: Resultsmentioning
confidence: 99%
“…However, pathogenic missense mutations have been described. Cheng et al showed that missense mutations located in the active sites produce a GSD III phenotype in which there is total or partial abolishment of GDE activity depending on the location of the mutation (Cheng et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, we expressed p.R1147G mutant and normal AGL proteins in COS cells transiently, and measured both glucosidase and transferase activities. 7 The p.R1147G exhibited negligible glucosidase activity, but retained 40% of transferase activity compared with wild AGL. p.R1147G might alter the tertiary conformation of the enzyme and slightly reduce the transferase activity.…”
Section: Discussionmentioning
confidence: 96%
“…In vitro functional analysis of p.R1147G, which was identified in patient 1, has been reported elsewhere. 7 A gene coding human glycogen debranching enzyme (gene symbol: AGL) has been shown to be 85 kb in length and composed of 35 exons, encoding a 7.0-kb mRNA. 8 Molecular analyses of GSD IIIa and IIIb have been performed in several ethnic populations and over 60 different AGL mutations have been reported to date (Human Gene Mutation Database; http://www.hgmd.cf.ac.uk/ac/index.php).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Missense mutations are scarce. 13,16,17 No mutation was prevalent, but c.348_373del26 was present in three mutant alleles (21%). Loss-of-function mutations in PHKA2 made up nearly 71% of the total; only 50% of the mutations deposited for this gene in the Human Gene Mutation Database belong to this category.…”
Section: Discussionmentioning
confidence: 99%